Where we are in treat to target era? Predictive factors for remission and drug switching in patients with axial spondyloarthritis: a real-life evidence from BioStaR nationwide registry - DURUÖZ, MEHMET TUNCAY; YAĞCI, İLKER (My University, 2022)
Objectives Factors associated with disease activity of axial spondyloarthritis (axSpA) and switching of biologic diseasemodifying anti-rheumatic drugs have not been clearly defned. We aimed to evaluate clinical characteristics of patients with axSpA, factors related to remission in treat to target era and predictive factors for biologic disease-modifying anti-rheumatic drug switching. Method A multicenter, observational cross-sectional study was performed between February 2019 and August 2019. We included all consecutive patients≥18 years with axSpA. Demographic and clinical variables were prospectively recorded. Clinical tools included Ankylosing Spondylitis Disease Activity Score with C-reactive protein (ASDAS-CRP), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Metrology Index (BASMI), and Maastricht Ankylosing Spondylitis Enthesitis Score (MASES). Results There were 969 patients with a mean age of 43.4±10.8 years. There were 143 patients (14.8%) with remission and 223 (23.1%) patients with low disease activity. Male sex (p=0.021), positive family history (p=0.036), and human leukocyte antigen-B27 (p=0.011) were predictors of remission by ASDAS-CRP. There were 654 patients (67.5%) who did not switch to another drug. The highest BASMI and MASES scores were calculated in patients with very high disease activity (p<0.05). In patients with drug switching, the disease duration was signifcantly higher (p<0.001) and the age at diagnosis was signifcantly lower (p=0.016). There were signifcantly more patients with uveitis and higher scores of MASES and BASMI in patients who switch to another biologic disease-modifying anti-rheumatic drugs (p=0.003, p=0.009, and p=0.004, respectively). Conclusions In patients with axSpA, male sex, younger age, and HLA-B27 positivity are associated with remission, while longer disease duration and accompanied uveitis appear to be related with drug switching. Clinical trial registration number and date NCT04139954/25.10.2019.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Rheumatology; Disease modifying anti rheumatic drugs; Drug switching; Remission induction; Spondyloarthritis; ANKYLOSING-SPONDYLITIS; DISEASE-ACTIVITY; INHIBITORS; THERAPY; HLA-B27